A SUBJECT MATTER SPECIALIST VERSUS STUDENTS’ MORAL GUARDIAN: EFL TEACHERS’ VOICES ON CHARACTER EDUCATION INCORPORATION INTO CLASSROOM INSTRUCTIONS - Noprianto, Eko; Suherdi, Didi; Muslim, Ahmad Bukhori (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
The degradation of morals among Indonesian young generation and the urgency of teaching both good competencies and strong characters to succeed in the 21st-century globally competitive society for them require all teachers including English teachers to incorporate character values into their classroom instructions as mandated in the 2013 curriculum. Given the fundamental roles teachers could serve in the success of promoting good character both outside and inside the classroom, it is critical to understand how they view such a program before they could bring it into the classroom. This qualitative case study scrutinizes how Indonesian English teachers perceive character education incorporation. Employing an interview, classroom observation, and lesson plan analysis, to two purposefully-selected English teachers from two different piloting schools, findings reveal that while they agree on the pivotal role they could serve toward students’ character development, they also emphasize the enhancement of some other factors, such as inspiring teachers, family, good leadership, the cohesiveness of school community members, media, and government supports for the success of character education reinforcement program in Indonesia.